A psychometric analysis of outcome measures in peripheral spondyloarthritis. Issue 7 (5th August 2015) - Turina, Maureen C; Ramiro, Sofia; Baeten, Dominique L; Mease, Philip; Paramarta, Jacqueline E; Song, In-Ho; Pangan, Aileen L; Landewé, Robert
Abstract : Objectives: To assess the discriminatory capacity of various outcome measures and response criteria in patients with peripheral spondyloarthritis (pSpA). Methods: Data originated from two randomised controlled trials, ABILITY-2 and Tnf Inhibition in PEripheral SpondyloArthritis (TIPES). Continuous outcome measures included patient's global assessment (PGA)/physician's global assessment of disease (PhGA), C-reactive protein (CRP), tender joint counts (TJC)/swollen joint counts (SJC), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and the Ankylosing Spondylitis Disease Activity Score (ASDAS). Dichotomous response criteria included Peripheral SpondyloArthritis Response Criteria (PSpARC), American College of Rheumatology (ACR), ASDAS and BASDAI response criteria. The capacity to discriminate between adalimumab and placebo groups was assessed by standardised mean differences (SMD) for continuous variables, and Pearson's χ 2 for dichotomous response criteria. Results: Within each trial, the composite indices for axial SpA assessment, ASDAS-CRP (SMD: −0.63 and −0.89 in ABILITY-2 and the TIPES trial, respectively) and BASDAI (SMD: −0.50 and −0.73), and the single-item measures PGA (SMD: −0.47 and −1.12) and PhGA (SMD: −0.64 and −0.87) performed better than other single-item measures, such as CRP (SMD: −0.18 and −0.53), SJC or TJC. In general, the PSpARC and ACR response criteria discriminated better than ASDAS and BASDAI response criteria. Conclusions: The axial SpA-specific ASDAS-CRP and BASDAI, but also PGA and PhGA, demonstrated good discriminatory ability in patients with pSpA. The pSpA-specific pSpARC response criteria and the rheumatoid arthritis-specific ACR response criteria also discriminated well. To fully capture typical pSpA manifestations, it may be worth developing new pSpA-specific indices with better performance and face validity. Trial registration numbers: ABILITY-2: NCT01064856 ; TIPES: EUDRACT 2008-006885-27.